A trustable software with a dynamic loop control mechanism. (1st January 2012) - Srirajun, Nalinrat; Bhattarakosol, Pattarasinee; Tantasanawong, Panjai; Han, Sunyoung
Unexpected infinite loop during software deployment period is an undesirable for every organisation since it can cause critical damages in various aspects. Most of the current protection methods will perform during the software development process using verification and validation processes. However, these methods will not cover the dynamic loop control mechanism where the termination of the loop is relied on the value obtained during runtime process. Thus, many possible error values cannot be protected based on human's limitation. Therefore, this paper proposes architecture for checking and terminating infinite loop situation during the runtime process. Additionally, the proposed mechanism can completely prevent the unlimited loop for these dynamic situations. The testing results have shown that the proposed solution provides the trustable system for every organisation.